2014
DOI: 10.1007/s00520-014-2298-9
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the financial burden of cancer: perspectives of older breast cancer survivors

Abstract: Purpose Financial burden among cancer survivors is often overlooked in survivorship care planning. Cancer survivors with limited incomes may be particularly affected. Yet, little data are available to address financial issues among them. Eliciting the survivors’ perspectives on how to deal with this financial burden is a first crucial step to identifying the means to provide this supportive care. Methods In this pilot study, three Nominal Group Technique (NGT) sessions were conducted with a convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…The implications these may have for the well-being of women with ovarian cancer, and how to address them, needs to be investigated. Breast cancer survivors, for example, suggested that knowing the costs of care upfront would help in dealing with financial challenges [22]. Similar interventions may also help women with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The implications these may have for the well-being of women with ovarian cancer, and how to address them, needs to be investigated. Breast cancer survivors, for example, suggested that knowing the costs of care upfront would help in dealing with financial challenges [22]. Similar interventions may also help women with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[2830] Most patients experience a fear of recurrence, [31] which is why individual tailored follow-up plans are needed instead of ready-made plans. We aimed to identify whether some patients might need continuous close surveillance whereas, in other patients, it might be possible to omit some tests or extend the intervals between surveillance tests.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐driven recommendations go beyond direct medical costs to address: psychosocial costs; indirect costs, such as employment losses; time costs; and nonmedical direct costs, such as transportation to medical visits . For example, one study of patient‐driven recommendations identified the need for affordable insurance, prompt information on costs, and access to social workers, navigators, and support groups knowledgeable about resources to reduce economic burden . However, that study only included older breast cancer survivors from one safety‐net clinic; therefore, an assessment of breast cancer survivors across age groups, insurance, and health care systems might yield new or different findings.…”
Section: Introductionmentioning
confidence: 99%